MRI-negative epilepsy : evaluation and surgical management - So, Elson L.; Ryvlin, Philippe (Cambridge : Cambridge University Press, 2015)
Drug-resistant epilepsy with negative MRI is frequently seen in patients considered for epilepsy surgery; however, clinical evaluation and surgical treatment is very complex and challenging. Advanced imaging techniques are needed to detect the location of the epileptogenic zone. In most cases, intracranial EEG recording is required to delineate the region of seizure onset - this carries some risks of major complications. Moreover, the borders between the recorded seizure onset and the location of important brain functions are often indistinct in MRI-negative epilepsy. Overall, the outcome of MRI-negative surgery is less favorable than that of MRI-positive surgery, but it can significantly improve with optimal management. Each chapter critically appraises the role and value of specific diagnostic and treatment techniques to address the challenges of MRI-negative epilepsy surgery. Authors critique evidence and share their expertise on the diagnostic options and surgical approaches that make epilepsy surgery possible and worthwhile in patients with this condition.
Title from publisher's bibliographic system (viewed on 13 May 2016).
Keywords: Treatment Outcome